Pengelolaan Sarana Dan Prasarana Laboratorium IPA Madrasah Aliyah Negeri 2 Karawang - Anisa Haffifa; Abdul Kosim (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2023)
Research conducted at MAN 2 Karawang, this study uses a qualitative approach. Discussed the management of science laboratory facilities and infrastructure at MAN 2 Karawang. The purpose of this study was to determine the management of facilities and infrastructure at MAN 2 Karawang. Where the management of educational facilities and infrastructure is the procurement and utilization to support optimal learning activities. And infrastructure is an important part of educational institutions and is one of the 8 national education standards. Based on the results of research in the management of laboratory facilities and infrastructure at MAN 2 Karawang has carried out the planning, maintenance and removal processes. From one of these processes, the maintenance process is the most important thing in the management of educational facilities and infrastructure. Because, the process can affect the ongoing learning activities / student practicum.